Predictors of non-adherence of hepatitis C patients to treatment: a systematic review - Ibrahim Adam, Samia; Md. Said, Salmiah; Daw, Mohamed Ali; Khalid, Bahariah; Kadir @ Shahar, Hayati (The International Journal of Health Sciences and Research, 2017)
Background: Predictors of non-adherence to treatment of the hepatitis C patients are complex and unclear. So far, there are limited studies that addressed these predictors. Objective: To identify the common predictors of non-adherence to treatment among hepatitis C patients. Methods: The authors reviewed literature on predictors or factors associated with non-adherence to treatment of hepatitis C patients that was published from 2007 to 2017 in PubMed, Proquest, Science Direct, Wiley, SAGE, and Ebscohost. The retrieved articles were subjected to inclusion criteria as follows: patients aged ≥ 18 years with chronic hepatitis C, patients treated with Pegylated interferon and Ribavirin, full text articles, quantitative designs, and the English language. All articles involving clinical trials were excluded from review. Results: Six studies were included in this review; five cohort studies and one cross-sectional study. Populations of these studies ranged from 72 to 5,760 individuals. According to STROBE checklist, representativeness of study sample and consideration of confounders were insufficient in most studies. Additionally, not all studies addressed potential sources of bias and applied adjusted analysis for confounders. Most studies examined condition-related factors that had negative effect on adherence to treatment like depression, psychiatric disorders and anemia. Another group of factors, i.e., patient-related factors, social and economic factors, therapy-related factors, and health care system-related factors were examined only by one study or two studies. Conclusion: Many factors have an influence on adherence and handling these factors, particularly in clinical sites, is very important for achievement of good adherence to hepatitis C treatment.